Myanmar: State, Community and the Environment - Skidmore, Monique (ANU Press, 2007)
Despite deteriorating economic and developmental conditions, worsening environmental problems, and troubles arising from the unresolved status of its ethnic minorities, Myanmar seems no closer to a political resolution. Myanmar's economy continues to stagnate, with severe implications for its people. Low levels of international assistance have exacerbated the situation. Myanmar-the state, community and the environment examines the missed opportunities by government and opposition groups to find a way out of the political impasse and improve the standard of living of the people of Myanmar. This collection provides insights into the country's economic development, in particular the vital rice-marketing sector and the attempts to expand existing industrial zones. It focuses, for the first time, on Myanmar's environmental governance with in-depth case studies, and on the increasing need for effective environmental protection and sustainability.